Modelling the influence of peri-urban trees in the air quality of Madrid region (Spain). - Alonso, Rocío; Vivanco, Marta G; González-Fernández, Ignacio; Bermejo, Victoria; Palomino, Inmaculada; Garrido, Juan Luis; Elvira, Susana; Salvador, Pedro; Artíñano, Begoña (Environmental pollution (Barking, Essex : 1987), 2011)
Tropospheric ozone (O(3)) is considered one of the most important air pollutants affecting human health. The role of peri-urban vegetation in modifying O(3) concentrations has been analyzed in the Madrid region (Spain) using the V200603par-rc1 version of the CHIMERE air quality model. The 3.7 version of the MM5 meteorological model was used to provide meteorological input data to the CHIMERE. The emissions were derived from the EMEP database for 2003. Land use data and the stomatal conductance model included in CHIMERE were modified according to the latest information available for the study area. Two cases were considered for the period April-September 2003: (1) actual land use and (2) a fictitious scenario where El Pardo peri-urban forest was converted to bare-soil. The results show that El Pardo forest constitutes a sink of O(3) since removing this green area increased O(3) levels over the modified area and over down-wind surrounding areas.
Keywords: Air Pollutants; Air Pollutants: analysis; Air Pollutants: metabolism; air pollution; Air pollution removal; Air Pollution: statistics & numerical data; Air quality models; Chemical; Cities; Dry deposition; Environmental Monitoring; Environmental Monitoring: methods; Models; Ozone; Ozone: analysis; Ozone: metabolism; Spain; Trees; Trees: classification; Trees: metabolism; Trees: physiology; Urban forest